GROWTH AND YIELD OF SESAME (Sesamum indicum L.) AS AFFECTED BY POULTRY MANURE, NITROGEN AND PHOSPHORUS AT SAMARU, NIGERIA - I. M. Haruna (Journal of Animal and Plant Sciences, 2011)
Field trials were conducted during the rainy seasons of 2005, 2006 and 2007 to study the growth and yield of sesame as affected by poultry manure, nitrogen and phosphorus. The experiments consisted of four levels of poultry manure (0, 5.0, 10.0, and 15.0 t ha-1), three levels of nitrogen in the form of urea (0, 60, and 120 kg N ha-1) and three levels of phosphorus in the form of single super phosphate (0, 13.2 and 26.4 kg P ha-1). The thirty six treatment combinations were laid out in a split-plot design with three replications. The factorial combination of N and P were assigned to the main plot while poultry manure was assigned to the sub-plot. The results showed that leaf area index and net assimilation rate were highest at 15 t ha-1 of poultry manure, 120 kg N ha-1 and 13.2 kg P ha-1. Grain yield per hectare was optimized at 5 t ha-1 of poultry manure, 60 kg N ha-1 and 13.2 kg P ha-1. Applications of 5 t ha-1 of poultry manure, 60 kg N ha-1 and 13.2 kg P ha-1 seems to be the ideal rates of poultry manure, nitrogen and phosphorus for increased yield of sesame in the northern guinea savanna agro ecological zone and is therefore recommended.
Keywords: Leaf area index; Crop growth rate; Net assimilation rate; Grain yield; Sesame.